Magazines currently : a matter of virtualisation - Ribeiro, Pedro Eduardo (2024)
Magazines are increasingly online and virtual and produce less material due to the different ongoing trends within the Portuguese magazine industry. Combining contributions from Organisational Communication Studies and the concept of virtual organisations with Magazine Studies, it is possible to inquire: how does the virtualisation of media organisations interfere with magazine production, circulation, and diffusion? The answer primarily refers to an increase of magazine virtualisation. Then, it points to a diversity of magazine trends: availability of press in digital editions, emergence of digital-native magazines, intensification of transmedia dynamics along with the development of digital technologies, or availability of websites of press-editions-based publications. Taking from international contexts and specificities of the national one, magazines, their virtualisation, and more wide-ranging magazine phenomena are under discussion in this essay, as well as challenges referring to current and future times.